AKTIVITAS ANTIOKSIDAN DARI EKSTRAK FENOLIK CORTEX UMBI UBI KAYU (Manihot esculenta) DAGING PUTIH DAN DAGING KUNING YANG DIAMBIL DARI KOTA MELONGUANE KABUPATEN KEPULAUAN TALAUD - Gagola, Christami (PHARMACON, 2014)
The purpose of this research is to determine the antioxidant activity of phenolic extracts of cassava tuber cortex white meat and yellow meat. Cortex cassava tubers extracted by methods reflux. After that, extract total phenolic content in the test. Determination of the free radical scavengers activities determined using DPPH (1,1-diphenyl-2-picrylhidrazil). The results of this study indicate that extracts of the cortex of cassava tubers and white flesh and yellow flesh contains total phenolic respectively 48.87 ± 0.057; 56.43 ± 0.174 mg / kg. Activities are free radical scavengers with DPPH showed that cassava tuber cortex extract yellow flesh has a radical antidote activity higher than white flesh extract. The result showed that phenolic extracts of cassava tuber cortex has antioxidant activity. Key words : antioxidants, cassava tuber cortex, phenolic extract